Molar heat capacities of the mixture {1,8-cineole + ethanol} at several temperatures and atmospheric pressure - Martínez-López, José F.; Schneider, Severin; Salavera, Daniel; Mainar, Ana M.; Urieta, José S.; Pardo, Juan I. (The journal of chemical thermodynamics, 2016)
Molar heat capacities at atmospheric pressure have been determined every 5K for the mixture {1,8-cineole (1)+ethanol (2)} in the temperature interval (304.7 to 324.5)K and the whole composition range with a Calvet type calorimeter Setaram C80. From the molar heat capacities, excess molar heat capacities have been calculated, their values being positive and increasing as the temperature rises. The solvation model COSMO-RS has been applied to predict the excess molar heat capacities. The model overestimates the values of the excess heat capacities but predicts well the trend of variation of the excess molar heat capacity with the temperature.